Prevalence of lower extremity peripheral arterial disease among diabetic patients and its relationship with quality of life (qol) in primary care: a single centre experience - Ab Hamid, Nurhayati; K. A., Nur Diyana; M. S., Muhaimin; Othman, Faidzal; Mahno, Noor Ezmas; Abdul Rahman, Muhammad Norhisham Azmi; Ahmad, Azrin Waheedy; Othman, Ahmad Faidzal (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2019)
Introduction: Peripheral Occlusive Arterial Disease (POAD) is an important cardiovascular morbidity especially among diabetics. The goal of the treatment is to improve patients’ quality of life (QoL) starting by quantifying the disease burden in our population especially among high risk group such as diabetics. Materials and Methods: This cross-sectional study aims to provide a data on the prevalence of POAD among diabetic population in a primary health care in Kuantan and its’ effects on the patient’s QoL. Additionally, we examined for any other stipulated associated factors that may have contributed towards the development of POAD. We applied a universal sampling for the purpose of patient selection. POAD is universally defined as ankle-brachial index (ABI) of lower than 0.9. Individuals were assessed on validated Malay version of WHOQOL BREF to assess their QoL parameters. P value of <0.05 considered as statistically significant. This study was registered with the National Medical Research Register (NMRR registration no. 17-1375-35710). Results: The prevalence of PAD among diabetic patients in Klinik Kesihatan (Local General Practitioner) Jaya Gading, Kuantan was found to be 20%. We found a significant relationship between lower levels of education (p = 0.016), older age group (p = 0.02) and lower economic class (p = 0.03) with the presence of POAD among diabetics. The presence of POAD has a significant adverse effect on QoL evidenced by lower Physical Domain (p=0.001), Psychological Domain (p=0.066), Social Domain (p=0.005), and Environmental Domain (p=0.027) scores using validated WHOQOL BREF questionnaires. Conclusion: The significant prevalence of POAD among diabetics prompts a greater urgency for early detection to prevent the development of its’ associated morbidity and deterioration of their QoL.